Comprehensive analysis of promoter-proximal RNA polymerase II pausing across mammalian cell types. Issue 1 (December 2016) - Day, Daniel; Zhang, Bing; Stevens, Sean; Ferrari, Francesco; Larschan, Erica; Park, Peter; Pu, William
Abstract Background For many genes, RNA polymerase II stably pauses before transitioning to productive elongation. Although polymerase II pausing has been shown to be a mechanism for regulating transcriptional activation, the extent to which it is involved in control of mammalian gene expression and its relationship to chromatin structure remain poorly understood. Results Here, we analyze 85 RNA polymerase II chromatin immunoprecipitation (ChIP)-sequencing experiments from 35 different murine and human samples, as well as related genome-wide datasets, to gain new insights into the relationship between polymerase II pausing and gene regulation. Across cell and tissue types, paused genes (pausing index > 2) comprise approximately 60 % of expressed genes and are repeatedly associated with specific biological functions. Paused genes also have lower cell-to-cell expression variability. Increased pausing has a non-linear effect on gene expression levels, with moderately paused genes being expressed more highly than other paused genes. The highest gene expression levels are often achieved through a novel pause-release mechanism driven by high polymerase II initiation. In three datasets examining the impact of extracellular signals, genes responsive to stimulus have slightly lower pausing index on average than non-responsive genes, and rapid gene activation is linked to conditional pause-release. Both chromatin structure and local sequence composition near the transcription start site influence pausing, with divergent features between mammals andDrosophila . Most notably, in mammals pausing is positively correlated with histone H2A.Z occupancy at promoters. Conclusions Our results provide new insights into the contribution of RNA polymerase II pausing in mammalian gene regulation and chromatin structure.